2019
DOI: 10.3201/eid2506.181027
|View full text |Cite
|
Sign up to set email alerts
|

Leishmaniasis in Norway Rats in Sewers, Barcelona, Spain

Abstract: We detected Leishmania infantum in 98 Norway rats ( Rattus norvegicus ) trapped in parks and sewers of Barcelona, Spain. The 84 rats from the sewers showed a prevalence of 33.3% and up to 2,272 estimated parasites. These results, in the most abundant potential reservoir in cities, is of public health concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…In addition to the found ZIP in the 100 examined rats, previous studies revealed that these same rats were infected by six additional zoonotic parasites, specifically, the protozoan Leishmania infantum (33.3% in sewers), the intestinal tapeworms Hymenolepis diminuta (33%) and H. nana (17%), the hepatic nematode Capillaria hepatica (17%), the oesophagic nematode Gongylonema neoplasticum (20%), and the intestinal acanthocephalan Moniliformis moniliformis (6%) [ 11 , 39 ]. Considering all the zoonotic parasites, protozoans and helminths, 95% of the rats were infected with at least one zoonotic species, i.e., almost 249,000 Norway rats carry some zoonotic parasite in the sewers of the studied city.…”
Section: Discussionmentioning
confidence: 91%
“…In addition to the found ZIP in the 100 examined rats, previous studies revealed that these same rats were infected by six additional zoonotic parasites, specifically, the protozoan Leishmania infantum (33.3% in sewers), the intestinal tapeworms Hymenolepis diminuta (33%) and H. nana (17%), the hepatic nematode Capillaria hepatica (17%), the oesophagic nematode Gongylonema neoplasticum (20%), and the intestinal acanthocephalan Moniliformis moniliformis (6%) [ 11 , 39 ]. Considering all the zoonotic parasites, protozoans and helminths, 95% of the rats were infected with at least one zoonotic species, i.e., almost 249,000 Norway rats carry some zoonotic parasite in the sewers of the studied city.…”
Section: Discussionmentioning
confidence: 91%
“…In Spain, and in addition to domestic dogs, leporids such as rabbits and hares have been demonstrated as competent reservoirs of the infection [ 67 ]. Micromammals (e.g., mice, shrews) seem to play a limited role in the epidemiology of the parasite [ 68 ], although an unanticipated high prevalence rate (33%) of the parasite has been recently described in rats captured in sewers in the city of Barcelona [ 69 ]. To confirm the accuracy and extent of these previous findings, we investigated by PCR the occurrence of Leishmania spp.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the two main vectors, Phlebotomus perniciosus and Phlebotomus ariasi , are known due to the monitoring of the city of Barcelona by the ASPB, the institution responsible for the vector surveillance and control in the city ( 42 ). Furthermore, recent research indicates that Norway rat, a synanthropic murid that shows high abundance and deeply distribution in the sewer system of the city ( 6 ), could play a relevant role as host reservoir of Leishmaniasis ( 43 ). At this point, it is important to emphasize the sewers have been also recorded as suitable breeding site for sandflies in Barcelona (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…In urban, periurban and domestic environments, dogs (Canis lupus familiaris) are usually considered main reservoirs of the parasite, although synanthropic rodents (e.g., Rattus norvegicus), wild rabbits (Oryctolagus cuniculus), hares (Lepus granatensis), and cats (Felis catus domesticus) can also play a relevant role as reservoir host (6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%